Slug frequency for a gas-liquid plug flow: Review and development of a new correlation. (November 2020) - Arabi, Abderraouf; Ragui, Karim; Salhi, Yacine; Filali, Abdelkader
Abstract: Slug frequency is one of the most important parameters for designing industrial installations where intermittent gas-liquid flows could be found. Thus, the literature is found full of various experimental investigations and developed empirical correlations to predict such parameter. Nevertheless, the effect of intermittent flow sub-regimes on slug frequencies remains an open issue, especially in the case of plug flow. Hence, the present work is devoted to providing an update review and analysis of the slug frequency in plug flow case. For this purpose, data from previous experiments have been collected and deeply examined. It was found that the increase in liquid superficial velocity and the decrease in pipe diameter could induce an increase of plug frequency. The comparison between experimental data and the predictions of twenty available empirical models showed that the correlations based on Strouhal number and input liquid fraction are the best ones that predict well the experimental plug frequency. However, each correlation is found to be valid for a limited range close to the data's conditions that were used for its development. As such, and by considering an extended range of the whole available experimental database, a new empirical correlation has been proposed.